Correlaton Between Family Spiritual Coping with Anxiety Level of the Patient’s in the Intensive Care Room - Novia Heriani; Hasniati Miradiah (Health Media, 2023)
The Intensive Care Unit is a special room for critically ill patients who require intensive care with or without hope for the patient to recover. In the patient's family, poor coping behavior will affect the way of communication and excessive behavior, thus affecting activities while waiting for patients. The purpose of this study was to determine the correlation between family spiritual coping and the level of anxiety of the patient's family in the ICU room. The research method was observational correlation with a cross sectional approach. The sample was the entire patient's family in the ICU Room as many as 69 respondents. Data were analyzed using the Spearman-Rho test. The results of statistical tests obtained p value (0.000) < (0.05) with a spearman rank value of - 0.660 which indicates the relationship both variables are very strong. So that the patient's family who has good spiritual coping also has mild anxiety.